Home health care of Iranian elderly with dementia: Study protocol for guideline adaptation - Alireza Irajpour; Fatemeh Maleki; Mohsen Shati; Mohamad R Najafii (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Advanced stages of dementia interfere with elderly self-care. Consequently, they need caregivers who take responsibility for their care in the long-term. Restrictions to the caregiver's access to information, resources, and organizational support have created problems in their caregiver role, which is why the World Health Organization (WHO) emphasizes caring for caregivers by providing evidence-based information and training programs. As there is no clinical practice guideline for home care in the Islamic Republic of Iran, this study aims to develop a home health care guideline for the elderly with dementia. MATERIALS AND METHODS: The ADAPTE process provided by the Guidelines International Network was considered as the basis. In order to identify the care needs of Iranian patients with dementia, semi-structured interviews were added to this guideline. DISCUSSION: The identification and implementation of the perspectives of patients and caregivers during the process of guidelines adaptation increase the applicability of the guidelines. Improved quality of life for the patients in their place of residence is one of the expected consequences of this guideline's implementation. The developed guidelines will be used at home health care centers, and dementia and Alzheimer's associations in Iran.